Pulmonary involvement in children with Langerhans cell histiocytosis - Çağrı Coşkun; Tezer Kutluk; Bilgehan Yalçın; Berna Oğuz; Diclehan Orhan; Ebru Yalçın; Eren Müngen; İnci Yaman Bajin; Uğur Özçelik; Burça Aydın; Nilgün Kurucu; Ali Varan; et al. (The Turkish Journal of Pediatrics)
Background. Pulmonary Langerhans cell histiocytosis (pLCH) is a rare disease, mostly a component of multisystemic LCH. We aimed to investigate the clinical features and treatment results in children with pLCH.